2019
DOI: 10.1111/liv.14091
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia reperfusion injury in liver transplantation: Cellular and molecular mechanisms

Abstract: Liver disease causing end organ failure is a growing cause of mortality. In most cases, the only therapy is liver transplantation. However, liver transplantation is a complex undertaking and its success is dependent on a number of factors. In particular, liver transplantation is subject to the risks of ischaemia‐reperfusion injury (IRI). Liver IRI has significant effects on the function of a liver after transplantation. The cellular and molecular mechanisms governing IRI in liver transplantation are numerous. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
269
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(276 citation statements)
references
References 157 publications
3
269
0
4
Order By: Relevance
“…Liver transplantation is often the sole treatment for end‐stage liver diseases, such as liver cirrhosis, late‐stage PSC and PBC, and liver cancers. However, liver transplantation has a risk of ischemia‐reperfusion injury (IRI), which is characterized by oxidative stress, inflammation, and liver damage, and IRI may lead to graft rejection . A previous study monitored blood pressure of 107 liver transplant recipients and found that approximately 90% of patients had arterial hypertension and abnormal circadian blood pressure pattern after operation .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplantation is often the sole treatment for end‐stage liver diseases, such as liver cirrhosis, late‐stage PSC and PBC, and liver cancers. However, liver transplantation has a risk of ischemia‐reperfusion injury (IRI), which is characterized by oxidative stress, inflammation, and liver damage, and IRI may lead to graft rejection . A previous study monitored blood pressure of 107 liver transplant recipients and found that approximately 90% of patients had arterial hypertension and abnormal circadian blood pressure pattern after operation .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…However, liver transplantation has a risk of ischemia-reperfusion injury (IRI), which is characterized by oxidative stress, inflammation, and liver damage, and IRI may lead to graft rejection. 97 A previous study monitored blood pressure of 107 liver transplant recipients and found that approximately 90% of patients had arterial hypertension and abnormal circadian blood pressure pattern after operation. 98 Another study analyzed 147 patients who underwent liver transplantation in one institution and found that 45 patients who had transplantation at night suffered higher incidence of intraoperative blood loss and other complications, postoperative abdominal infection, longer operation time, and longer time to restore liver functions after transplantation compared to 102 patients with daytime operation.…”
Section: Liver Transplantation and Ischemiareperfusion Injurymentioning
confidence: 99%
“…The traditionally accepted model of liver IRI involves a period of cold IRI whilst the donor liver is being procured, followed by a period of warm IRI during the implantation phase of transplantation [10]. It is important to note that much of the basic and translational research performed in this area has involved models of warm IRI, predominantly in small animal experiments [11].…”
Section: The Mechanism Of the Liver Ischaemia-reperfusion Injurymentioning
confidence: 99%
“…It is important to note that much of the basic and translational research performed in this area has involved models of warm IRI, predominantly in small animal experiments [11]. This difference has important implications for biomarker discovery, validation and utility, which is further compounded by the fact that cold and warm IRI most likely have variable effects in different types of donor livers [10]. The IRI encompasses a very complex and broad-based injury that still remains to be completely understood, and it should be considered and assessed within the context of the triggering insult and the type of graft exposed to the injury.…”
Section: The Mechanism Of the Liver Ischaemia-reperfusion Injurymentioning
confidence: 99%
See 1 more Smart Citation